2011
DOI: 10.1063/1.3633116
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of voltage-dependent series resistance from I-V characteristics of Schottky diodes

Abstract: A method for extracting the bias dependent behaviour of the series resistance of a Schottky barrier diode from experimental I-V data is presented. It was assumed that the behaviour of the Schottky barrier is well defined by thermionic emission theory. Relative merit of the method was determined by applying the method on some artificial sets of I-V data corresponding to known values of series resistances and comparing the results with existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The diode current current I in a Schottky diode in the presence of appreciable diode series resistance R s is cyclically dependent on itself, the applied voltage V , the absolute diode temperature T , effective barrier height φ , the ideality factor n [12,13,14]. That is,…”
Section: The Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…The diode current current I in a Schottky diode in the presence of appreciable diode series resistance R s is cyclically dependent on itself, the applied voltage V , the absolute diode temperature T , effective barrier height φ , the ideality factor n [12,13,14]. That is,…”
Section: The Hypothesismentioning
confidence: 99%
“…MS device parameters are known to depend on factors such as applied bias and junction temperature [13,20]. The complexity of the MS diode equation is the foremost reason for the existence of the many extraction methods and their varied simplifying assumptions.…”
Section: Case I -Constant Barrier Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, Kiuru et al [53] has suggested another new model for the thermal resistance and series resistance of a SBD. Durmuş and Atav [54] have suggested a method for determining the bias dependent behavior of the series resistance of a SBD from the I − V data by help of TE equations. They [54] have made definition of the relative merit of the method by applying the method on some artificial I − V data sets corresponding to known R s values and comparing their own conclusions with the other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Durmuş and Atav [54] have suggested a method for determining the bias dependent behavior of the series resistance of a SBD from the I − V data by help of TE equations. They [54] have made definition of the relative merit of the method by applying the method on some artificial I − V data sets corresponding to known R s values and comparing their own conclusions with the other methods. Recently, Oruç and Altındal [50] have applied Norde [43], Bohlin [45], Mikhelashvili [55], and Cheung [40] methods to I -V data to determine the main parameters of a SBD.…”
Section: Introductionmentioning
confidence: 99%